Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I am attempting to derive the Riccati Equation for linear-quadratic control. The original equation is:

$-\partial V/\partial t = \min_{u(t)} \{x^TQx + u^TRu + \partial V^T/\partial x(Ax + Bu) \}$

$x \in \Re^n$, $u \in \Re^m$, $Q \in \Re^{n\times n}$, $R \in \Re^{m\times m}$, $A \in \Re^{n\times n}$, $B \in \Re^{n\times m}$.

It can be shown that the minimal $u$ is $u^*=-\frac{1}{2}R^{-1}B^T\partial V/\partial x$; also, $V(x,t)$ can be shown to be quadratic in $x$, so it is of the form $V(x(t),t) = x(t)^{T}P(t)x(t)$, so $\partial V/\partial x = 2P(t)x(t)$. Thus $u^*(t) = -R^{-1}B^TP(t)x(t)$. We'd like to solve for $P$, which is symmetrical.

Plugging into the original equation, I obtain

$-\partial V/\partial t = -x^T\dot{P}x \equiv x^TQx + (-R^{-1}B^TPx)^TR(-R^{-1}B^TPx)+2x^TP(Ax+B[-R^{-1}B^TPx])$

Somehow this gets reduced to

$-x^T\dot{P}x = x^T\{A^TP + PA + Q - PBR^{-1}B^TP\}x$

I cannot figure out the manipulation to get to the final equation. In particular, how is there both an $A^TP$ and $PA$ term in the final expression, when I distribute $2x^TP$ into $Ax+Bu^*$? Any insight would be helpful. Thanks.

share|improve this question

1 Answer 1

up vote 1 down vote accepted

$P$ is real symmetric and so is diagonalizable: $P = QLQ^T$ with some orthogonal $Q$.

Then, $$\begin{align*} A^TP+PA &= A^TQLQ^T + QLQ^TA \\ Q^TA^TP+Q^TPA &= Q^TA^TQLQ^T+LQ^TA \\ Q^TA^TPQ+Q^TPAQ &= Q^TA^TQL+LQ^TAQ \\ Q^T(A^TP+PA)Q &=Q^TA^TQL+(Q^TAQ)^TL \\ &= Q^TA^TQL+Q^TA^TQL \\ &= 2(Q^TA^TQ)L \end{align*} $$

Moving back the $Q$'s from the left-hand side,

$$\begin{align*} A^TP+PA &= 2Q(Q^TA^TQ)LQ^T \\ &= 2A^T(QLQ^T)\\ &= 2A^TP \\ &= 2PA \end{align*} $$

Associativity of matrix operations and the symmetry of $P$, namely $P^T=P$, are exploited a few times here.

share|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.